Feasibility of a hip flexion feedback system for controlling exercise intensity and tibia axial peak accelerations during treadmill walking - Oliveira, N.; Chiu, C.-Y. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2024)
The ability to meet high exercise intensities is limited by the increased risk of injury in some clinical populations. Previous studies have linked large tibia peak positive accelerations resulting from running to increased risk of developing lower-extremity injury. The purpose of this study is to determine the feasibility of using a hip flexion feedback system (HFFS) to meet and maintain different exercise intensities while maintaining low tibia axial accelerations. Ten healthy participants were tested on a HFFS test and an independent walking/running test to meet exercise intensities of 40% and 60% of heart rate reserve (HRR). During the HFFS test, the HFFS controlled in real time the exercise intensity by directing individuals to specific maximum hip flexion targets during walking and providing visual information that assists them in maintaining low tibia peak positive accelerations during the initial contact phase. Maximum hip flexion targets during walking are calculated based on real-time readings of the participant`s heart rate. During the independent test, exercise intensity was controlled independently by the participant using treadmill speed. Compared to the independent test, using the HFFS at 60% HRR resulted in similar heart-rate error but lower tibia peak positive accelerations. No differences were observed for the 40% HRR intensity. This paper describes a novel exercise approach that uses the individual`s heart rate to calculate maximal hip flexion targets that an individual should meet during treadmill walking. The HFFS also provides tibia peak positive peak acceleration cues. Therefore, the HFFS can increase and control exercise intensities while maintaining low tibia accelerations. In particular, the HFFS might be an alternative strategy to meet moderate to vigorous exercise intensities in populations at risk of developing lower-extremity injuries.